2018
DOI: 10.5194/nhess-18-857-2018
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between precipitation and insurance data for floods in a Mediterranean region (northeast Spain)

Abstract: Abstract. Floods in the Mediterranean region are often surface water floods, in which intense precipitation is usually the main driver. Determining the link between the causes and impacts of floods can make it easier to calculate the level of flood risk. However, up until now, the limitations in quantitative observations for flood-related damages have been a major obstacle when attempting to analyse flood risk in the Mediterranean. Flood-related insurance damage claims for the last 20 years could provide a pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 42 publications
5
38
0
Order By: Relevance
“…The decrease becomes larger with higher levels of global warming. This pattern is also observable in other studies of the Mediterranean region (Jacob et al, 2014;Cramer et al, 2018;Sillmann et al, 2013;Rajczak and Schär, 2017;Turco et al, 2017). For example, Kjellström et al (2018) found an increase in mean precipitation in the north of Europe but a reduction in the south, especially during summer months.…”
Section: Extreme Precipitation Projectionssupporting
confidence: 78%
See 3 more Smart Citations
“…The decrease becomes larger with higher levels of global warming. This pattern is also observable in other studies of the Mediterranean region (Jacob et al, 2014;Cramer et al, 2018;Sillmann et al, 2013;Rajczak and Schär, 2017;Turco et al, 2017). For example, Kjellström et al (2018) found an increase in mean precipitation in the north of Europe but a reduction in the south, especially during summer months.…”
Section: Extreme Precipitation Projectionssupporting
confidence: 78%
“…In the last few years, much research has focused on the study of climate change in the Mediterranean region, an area that is identified as highly vulnerable to climate change according to the "Fifth Assessment Report" of the Intergovernmental Panel on Climate Change (IPCC, 2014). Some studies have found an increase in precipitation extremes with global warming projections in the Mediterranean region (Colmet-Daage et al, 2018;Drobinski et al, 2018), although a general decrease in the annual precipitation is projected (Jacob et al, 2014;Cramer et al, 2018;Sillmann et al, 2013;Rajczak and Schär, 2017). Cramer et al (2018) state that future warming in the Mediterranean region is expected to exceed the global mean rates by 25 %, with peaks of 40 % in summer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hurford et al [33] evaluated the return periods of rainfall thresholds that are used for warnings by linking rainfall intensities with observed SWFs using data from fire and rescue services. Cortès et al [34] analyzed the relationship between flood-related insurance claims and heavy precipitation at the postal code level using daily precipitation accumulations. However, this study did not differentiate between FFs and SWFs.…”
Section: Introductionmentioning
confidence: 99%